Seasonal variations in diversity and the relative abundance of Odonata naiads from the temporary pools in Basrah Province-Southern of Iraq - Ahmed, Huda K.; Kareem, Dhia K. (Iraqi Journal of Aquaculture, 2021)
This study aimed to investigate the monthly changes in the diversity and abundance of Odonata naiad's species for the period from December 2017 to November 2018 from three temporary pools in different areas of Basrah Province, including Abu Gossra-Abu Al-Kassib District (station 1), Al-Masehab- Al-Hartha district (station 2) and Al-Jalal - Al-Madina District (Station 3). Some environmental factors were measured, as water temperatures ranged between (12-38 ° C) while the salinity ranged between (1.2-14 ‰). Ten species of Odonata naiads were recorded, including eight species of Suborder Anisoptera and two species of Suborder Zygoptera. The highest diversity of naiads (9 species) was in St.1 and St.2, and the lowest diversity (8 species) was in St.3. Statistical analysis showed significant effect of environmental factors on the abundance of naiads during sampling period between stations and months. The highest relative abundance was 70% for Crocothemis servilia during January, while the lowest relative abundance was 0.98. % for Diplacodes lefebvrei during April. Environmental indexes of Anisoptera naiads in Basrah showed that their communities are poor in diversity and turbulent, balanced or semi balanced according to the standard values. Jacquard index showed the highest qualitative similarity between St.2 and St.3, and the lowest between St.1 and St.2.